L-Tryptophan, Melatonin, Serotonin Profiles in the Foods and their Effects on Health - Seda Kurtulmuş; Tuğba Kök Taş (Turkish Journal of Agriculture: Food Science and Technology)
Nowadays, depending on the progress of science and technology, our eating habits have changed. The shape and quality of nutrition is important for human health. Especially, some food components have various effect on central nervous system such as depression, anxiety, sleep, appetite. Food constituents are transported into the central nervous system via the neutral amino acids such as phenylalanine, leucine, isoleucine, tyrosine and valine. Amino acids have an important role in human nutrition. It cannot be synthesized in the body and one of the essential amino acids that must be taken outside, trytophan, is indispensable in human nutrition because of it has the many functions. In recent years, scientific community concentrated on the various functions of L-Trytophan (L-Trp) as pioneer in the secretion of the hormones serotonin and melatoninin in the human body. The hormones serotonin and melatonin is responsible for activities such as psychology, sleep, body temperature, blood pressure balance, antioxidant effect, cancer inhibitor, sexuality, autism and circadian rhythms in human body that they are available in various foods such as milk, kefir, yogurt, orange, strawberry, grape, olive oil, walnut, prune, nut, pomegranate, coffee, kiwi and banana. In this study, L-Trp, serotonin and melatonin biosynthesis and metabolism, food profiles and in terms of their physiological and biological effects on human health has been compiled.